Structural and Functional Lexical Bundles in Woman’s Hour Daily Podcast Interview at Bbc Radio 4 (The Journal of Educational Development, 2021)
lexical bundles are sequences of words that are arranged or used together in natural spoken or written discourse. The expression of lexical bundles can indicate what native usually say and or write in certain register. The objective of this study is to explain the existence of structural and functional lexical bundles in Woman’s Hour Daily Podcast Interview. This current study used qualitative study with the design of discourse analysis, particularly spoken text analysis The object of this study were presenters’ and guests’ conversation in the “woman’s hour daily podcast interview on BBC Radio 4. The result revealed that the finding showed that from a total of 151 lexical bundles found in conversation, the most dominant structural form of the lexical bundle in the interview conversation is verb phrase in the form of 1st and 2nd person pronoun +verb phrase, and the most dominant functional form is stance bundles in the form of desire.